Best practices and getting started guide for Oracle on IBM LinuxONE - Adamovich, Susan; Amsavelu, Sam; Jagarlamudi, Srujan; Malige, Raghu; Morgan, Michael; Novak, Paul; Simpson, David J. (IBM Redbooks, 2020)
IBM® is a Platinum level Partner in the Oracle Partner Network, which delivers the proven combination of industry insight, extensive real-world Oracle applications experience, deep technical skills, and high-performance servers and storage to create a complete business solution with a defined return on investment. From application selection, purchase, and implementation to upgrade and maintenance, we help organizations reduce the total cost of ownership and the complexity of managing their current and future applications environment while building a solid base for business growth. Oracle Database running on Linux is available for deployment on IBM LinuxONE by using Redhat Enterprise Linux (RHEL) or SUSE Linux Enterprise Server (SLES). This enterprise-grade solution is designed to add value to Oracle Database solutions. This IBM Redpaper® publication focuses on accepted good practices for installing and getting started by using Oracle Database, which provides you with an environment that is optimized for performance, scalability, flexibility, and ease-of-management.
Online resource; title from title details screen (O'Reilly, viewed February 15, 2022)
Keywords: Oracle (Computer file); Linux; Information storage and retrieval systems; Database management; Open source software; Information Systems; Systèmes d'information; Bases de données; Gestion; Logiciels libres